A quantum-chemical approach to Ni and Fe codoping in SnO2 - Stashans, A. (2016)
© 2016 World Scientific Publishing Company Density functional theory and generalized gradient approximation using a Hubbard-like term was employed to study tin dioxide material containing an oxygen vacancy as an intrinsic defect and being codoped simultaneously with Fe and Ni atoms. Results on atomic displacements, electronic and magnetic features are obtained and discussed for different configurations taking into consideration relative impurityimpurity as well as impurityvacancy positions. It appears that Fe atom addition to the system enlarges considerably a local magnetic moment due to the strong magnetic coupling between the Fe (Formula presented.) and O 2p states for the (Formula presented.) spin subsystem.